CONTRAST-ENHANCED COMPUTED TOMOGRAPHIC CHOLANGIOGRAPHY IN DIFFERENTIAL DIAGNOSIS OF THE MALIGNANT AND BENIGN CAUSES OF BILIARY OBSTRUCTION - V. V. Zarubin; A. P. Kurazhov; V. D. Zavadovskaja; O. V. Rodionova; O. S. Tonkikh; I. Yu. Klinovitskiy; M. A. Zorkaltsev; V. I. Haritonkin (Сибирский онкологический журнал, 2021)
Introduction. Determination of the cause of cholestasis and treatment of patients with obstructive jaundice syndrome remains challenging owing to the steady rise in diseases of the hepatopancreatoduodenal zone and the high frequency of diagnostic errors. In the differential diagnosis of the causes of obstructive jaundice, diagnostic imaging techniques are of the greatest importance. In the world literature, there are few reports on the assessment of the diagnostic potential of multispiral computed tomography under conditions of direct contrasting of the biliary tree using endoscopic retrograde cholangiopancreatography, percutaneous transhepatic cholangiography, or through pre-installed palliative drainage in the bile ducts. There is no generally accepted algorithm for determining the causes of biliary obstruction. It leads to ineffective use of various diagnostic imaging techniques, complicating the diagnostic process.The purpose of the study was to evaluate the diagnostic efficacy of contrast-enhanced ct cholangiography (ct-cg) in the differential diagnosis of causes of malignant and benign biliary obstruction in cases with obstructive jaundice syndrome.Material and methods. The study included 55 patients with obstructive jaundice, who were treated in a surgical hospital from july 2016 to july 2019.Results. It was found that contrast ct-cg in diagnosing the causes of biliary obstruction of both malignant and benign genesis is more informative than x-ray endoscopic retrograde cholangiopancreatography. The diagnostic efficacy of ct-cg in detecting causes of malignant biliary obstruction was: 93.3% sensitivity, 92.9% specificity, and 93.1% accuracy. The diagnostic efficacy of ct-cg in detecting causes of benign biliary obstruction was: 92.9%, 93.3% and 93.1%, respectively.Conclusion. Based on the high accuracy, contrast-enhanced ct-cg is a promising imaging technique in cases with bile duct obstruction.